Atypical presentations of DYT1 dystonia with acute craniocervical onset. (February 2021) - Pavelekova, P.; Jech, R.; Zech, M.; Krepelova, A.; Han, V.; Mosejova, A.; Liba, Z.; Urgosik, D.; Gdovinova, Z.; Havrankova, P.; Fecikova, A.; Winkelmann, J.; et al.
Abstract: DYT1 gene mutations lead to early-onset dystonia that begins with focal limb onset and spreads to other body regions within 5 years, with typical sparing of the oromandibular muscles. In the present study, we describe two patients with an unusual presentation of the disease.